ANALISIS KEBUTUHAN RUANG TERBUKA HIJAU BERDASARKAN KEBUTUHAN OKSIGEN DI KOTA SALATIGA - Gurit, Sujendra Wijang; Sutrisno, Alfred Jansen (Agros Journal of Agriculture Science, 2024)
The oxygen demand in Salatiga city is increasing due to the increasing of population and vehicles. This oxygen can be met if the development of Green Open Space (GOS) is growing, However, this has not been well identified how many GOS are needed for oxygen demands in the city of Salatiga. The purpose of this research is to identify how many green open spaces are needed in Salatiga city based on the oxygen demand there. This research uses a quantitative descriptive method by calculating the area of land use included in the category of GOS, and calculating the oxygen demand of citizens and motorized vehicles. In determining the need for green space, calculations are carried out using the Gerarkis formula to obtain the results of green space needs by calculating the green space based on oxygen demand. Based on the analysis of land use, the total GOS in 2023 for the city of Salatiga was 1,046.21 hectares which consists of green belt, horticultural areas, plantation areas, local protection areas, cemeteries, urban forests and parks. The trend of oxygen demand increases in line with the population growth from 2018 to 2022; along with increasing motorized vehicles, while buses have decreased due people are not willing to use public transport. It can be concluded that the existing green spaces in Salatiga City cannot meet the oxygen demand of the population and motorized vehicles. Where the green space area must be increased to meet oxygen demand based on population and motor vehicle data in 2023 is 267.21 hectares